Pemberhentian Tidak Dengan Hormat Pegawai Negeri Sipil karena Tindak Pidana Korupsi: Perspektif Fiqh Siyasah (Analisis Putusan PTUN No. 4/G/2019/PTUN.PDG) - Syah, Cerah Andika; Marpaung, Zaid Alfauza (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study examines the dishonorable dismissal of civil servants in cases of corruption by analyzing its legal and political dimensions from the perspective of fiqh siyasah. The research adopts a normative juridical method with a legislative, conceptual, and case approach, focusing on the decision of the Regent of Sijunjung regarding the plaintiff’s dismissal. The problem addressed in this study is whether the dismissal was consistent with legal certainty and the principles of justice under both national law and Islamic political jurisprudence. The findings indicate that the Regent’s decision created legal uncertainty and conflicted with the principle of rechtmatigheid, as no dictum revoked the prior decision reinstating the plaintiff, leaving both decisions simultaneously valid. Furthermore, the dismissal was based on retroactive application of Law No. 5/2014, Government Regulation No. 11/2017, and the Decree of Three Ministers, which contradicts Article 28I paragraph (1) of the 1945 Constitution and the general principles of good governance. From the perspective of fiqh siyasah, the retroactive application is inconsistent with the principles of justice (al-‘adl), legal certainty (al-yaqin), benefit (al-mashlahah), accountability (mas’uliyyah), and transparency (ash-shafafiyyah). This study concludes that dishonorable dismissal in this case undermines both state law and Islamic political ethics, highlighting the need for consistency, fairness, and non-retroactivity in public service governance.‎